PENGGUNAAN SEKURITAS TERSEDIA UNTUK DIJUAL DALAM MANAJEMEN LABA DAN MANAJEMEN RASIO KECUKUPAN MODAL - sungkowo, wulandari (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2024)
The purpose of this study is to examine whether Indonesian bankings practice earning and capital adequacy ratio management using available for sale- securities. Samples were 30 banks selected by purposive sampling method from conventional banking companies listed in Indonesia Stock Exchange during the observation period 2011-2013. This study use two multiple linear regression models. The first model is about to detect bank manager use available for sale-securities to manage earning. Meanwhile, the second model is about to detect bank manager use available for sale-securities to manage capital adequacy ratio. The results of this study indicate that manager using available for sale-securities to manage earnings. However, manager doesn't use available for sale-securities to manage capital adequacy ratio. These findings indicate that managers use sale of available for sale securities to manage earning in bank.